Magnetic Solid Phase Extraction for Determination of Dyes in Food and Water Samples - Ruba Fahmi Abbas; Mohammed Jasim Mohammed Hassan; Ahmed Mahdi Rheima (Indonesian Journal of Chemistry, 2023)
Recently, magnetic solid-phase extraction (MSPE) is an important technology due to its use in analytical chemistry, biotechnology, and medicinal fields. MSPE shows rapid isolation of target analyte from large volume samples, the huge surface area of magnetic nanoparticles (MNPs), and simplicity in application due to using an external magnetic field instead of using packing column, centrifuge and filter papers. The aim of this review is to evaluate the extraction and determination of dyes in food and water samples by using the MSPE technique.